2019
DOI: 10.1021/acscatal.9b02264
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Electronic Tuning of Ni2P through Iron Doping toward Highly Efficient Water Splitting

Abstract: Efficient water electrolysis for hydrogen production constitutes a key segment for the upcoming hydrogen economy, but has been impeded by the lack of high-performance and low-cost electrocatalysts for, ideally, simultaneously expediting the kinetics of both hydrogen and oxygen evolution reactions (HER and OER). In this study, the favored binding energetics of OER and HER reaction intermediates on iron-doped nickel phosphides are first predicted by density functional theory (DFT) simulations, and then experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(156 citation statements)
references
References 63 publications
3
147
0
Order By: Relevance
“…Besides, generally, doping heteroatoms into electrocatalysts could effectively tune their electronic structure and improve their conductivity. In this context, various metal‐ or non‐metal‐doped MOF‐derived materials have been developed and exhibit the significantly enhanced electrocatalytic performance in contrast with their pristine materials. However, there is rarely a report about doping heteroatoms into direct MOF materials for electrocatalytic water splitting.…”
Section: Methodsmentioning
confidence: 88%
“…Besides, generally, doping heteroatoms into electrocatalysts could effectively tune their electronic structure and improve their conductivity. In this context, various metal‐ or non‐metal‐doped MOF‐derived materials have been developed and exhibit the significantly enhanced electrocatalytic performance in contrast with their pristine materials. However, there is rarely a report about doping heteroatoms into direct MOF materials for electrocatalytic water splitting.…”
Section: Methodsmentioning
confidence: 88%
“…As reported, the resulting high valence Co and Fe act as the active sites, facilitating the formation of peroxide intermediates during OER (Table S2). [20,31,32] Inspired by the remarkable HER and OER catalytic performances by choosing CoFeP@Ru, we further assembled an electrolyzer in two-electrode system with CoFeP@Ru in both the cathode and anode to test the overall water splitting. [32] As show in Figure 4e, among CoP, CoP@Ru, CoFeP@Ru electrodes, the electrolyzer with CoFeP@Ru electrodes affords the highest activity with the need for a cell voltage of � 1.76 V to drive the current density of 10 mA cm À 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Moreover, previous experimental and theoretical work has reported that the incorporation of foreign metal atoms could optimize the absorption kinetic energy barrier of OER intermediates, accelerating the sluggish OER. [19][20][21] Consequently, the incorporation of metal atoms should be an efficient strategy for the modification of OER activity in TMDs.…”
Section: Doping Engineering Has Been An Important Approach To Boost Omentioning
confidence: 99%
“…The introduction of metal atoms with similar atomic radius and electron configuration could induce subtle distortion of the atomic arrangement via the inevitable generation of a locally unbalanced Coulomb force, which could engineer the creation of additional exposed active sites 16–18. Moreover, previous experimental and theoretical work has reported that the incorporation of foreign metal atoms could optimize the absorption kinetic energy barrier of OER intermediates, accelerating the sluggish OER 19–21. Consequently, the incorporation of metal atoms should be an efficient strategy for the modification of OER activity in TMDs.…”
Section: Introductionmentioning
confidence: 99%